2014
DOI: 10.1007/s11695-014-1177-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Laparoscopic Sleeve Gastrectomy in Patients Older than 60 Years

Abstract: LSG is safe and very efficient in patients aged >60, despite higher rates of perioperative comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…Another recent study comparing the patients over 60 years with those under 50 years for up to 22 months after LSG showed better results in the younger age group for %EBMIL. The study did not address the ages between 50 and 60 years, and benefits from cutting out that group to make a more clear distinction, suggesting 55 years is arbitrary at best [37] [ Remark 7]. …”
Section: Discussionmentioning
confidence: 99%
“…Another recent study comparing the patients over 60 years with those under 50 years for up to 22 months after LSG showed better results in the younger age group for %EBMIL. The study did not address the ages between 50 and 60 years, and benefits from cutting out that group to make a more clear distinction, suggesting 55 years is arbitrary at best [37] [ Remark 7]. …”
Section: Discussionmentioning
confidence: 99%
“…We also identified two more deaths due to carcinomas in the RYGB group. Although Mizrahi et al [8] concluded LSG is safe for patients aged >60, they reported a high overall complication rate of 32.5 % in their 52 patients. Spaniolas et al [9] recently reported no difference in early morbidity rate between LSG and laparoscopic RYGB in patients older than 65.…”
Section: Discussionmentioning
confidence: 83%
“…LAGB laparoscopic adjustable gastric banding, LSG laparoscopic sleeve gastrectomy, RYGB Roux-en-Y gastric bypass, EWL percentage of excess weight loss, mo months literatures examine the result of RYGB or LAGB, and limited data exist on LSG procedures in the elderly as it is a fairly new procedure in the bariatric field. However, some have advocated its safety for the elderly [8,9,13]. In our current study, we compared the outcomes of LAGB, LSG, and RYGB procedures in terms of complication, weight loss, and comorbidity resolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No primary studies met the full criteria for inclusion in this review. Ten manuscripts reporting on bariatric surgery studies were identified in which data were reported in older patients, although the studies were not specifically designed to report on the outcomes of bariatric interventions in 641 older patients with T2DM or other comorbidities (Table 1) [ [16][17][18][19][20]24]. Four registry studies were identified in which data were reported on older patients, which yielded little efficacy data but did yield postoperative mortality and 30-day complication rates in 6837 patients.…”
Section: Resultsmentioning
confidence: 99%